Rising Informality - Palmade, Vincent; Anayiotos, Andrea (World Bank, Washington, DC, 2012)
By some estimates more than 30 percent of the developing world's GDP and 70 percent of its workers are outside the official economy. The implications: Most small firms are trapped in low-productivity operations with little access to finance, key government services, and formal customers. Workers lack safety and social protection. And bigger, better-connected firms use unfair informal practices to beat out more productive formal competitors. The result is slower economic growth and a growing social divide between the informal and formal parts of society.